Endothelial p300 Promotes Portal Hypertension and Hepatic Fibrosis Through C‐C Motif Chemokine Ligand 2–Mediated Angiocrine Signaling. Issue 6 (19th April 2021) - Gao, Jinhang; Wei, Bo; Liu, Mengfei; Hirsova, Petra; Sehrawat, Tejasav S.; Cao, Sheng; Hu, Xiao; Xue, Fei; Yaqoob, Usman; Kang, Ningling; Cui, Huarui; Pomerantz, William C.K.; et al.
Abstract : Background and Aims: During liver fibrosis, liver sinusoidal endothelial cells (LSECs) release angiocrine signals to recruit inflammatory cells into the liver. p300, a master regulator of gene transcription, is associated with pathological inflammatory response. Therefore, we examined how endothelial p300 regulates angiocrine signaling and inflammation related to portal hypertension and fibrogenesis. Approach and Results: CCl4 or partial inferior vena cava ligation (pIVCL) was used to induce liver injury. Mice with LSEC‐specific p300 deletion ( p300 LSECΔ/Δ ) or C‐C motif chemokine ligand 2 ( Ccl2 ) deficiency, nuclear factor kappa B ( NFκB )– p50 knockout mice, and bromodomain containing 4 (BRD4) inhibitors in wild‐type mice were used to investigate mechanisms of inflammation regulation. Leukocytes were analyzed by mass cytometry by time‐of‐flight. Epigenetic histone marks were modified by CRISPR endonuclease‐deficient CRISPR‐associated 9‐fused with the Krüppel associated box domain (CRISPR‐dCas9‐KRAB)–mediated epigenome editing. Portal pressure and liver fibrosis were reduced in p300 LSECΔ/Δ mice compared to p300 fl/fl mice following liver injury. Accumulation of macrophages was also reduced in p300 LSECΔ/Δ mouse livers. Ccl2 was the most up‐regulated chemokine in injured LSECs, but its increase was abrogated in p300 LSECΔ/Δ mice. While the macrophage accumulation was increased in NFκB‐p50 knockout mice with enhanced NFκB activity, it was reduced in mice with LSEC‐specific Ccl2 deficiency and mice treated with specific BRD4 inhibitors. In vitro, epigenome editing of CCL2 enhancer and promoter regions by CRISPR‐dCas9‐KRAB technology repressed TNFα‐induced CCL2 transcription through H3K9 trimethylation. In contrast, TNFα activated CCL2 transcription by promoting p300 interaction with NFκB and BRD4, leading to histone H3 lysine 27 acetylation at CCL2 enhancer and promoter regions. Conclusions: In summary, endothelial p300 interaction with NFκB and BRD4 increases CCL2 expression, leading to macrophage accumulation, portal hypertension, and liver fibrosis. Inhibition of p300 and its binding partners might serve as therapy in the treatment of liver diseases.